Module 4: Basic Counselling Skills for Teachers - Mansor, Norwati; Wan Yusoff, Wan Mazwati (2021)
This module aims to train teachers in basic counselling skills to help students to be self-aware, to understand their own potential, and to guide them in making good choices and decisions in life. To do so teachers are required to be skilful in communication, interpersonal relations, ethics, problem-solving, doing research, observation, reasoning, and they too need to be skilful in using computers. Furthermore, teachers should have emotional stability, compassion, be trustworthy, open-mindedness and patient.